Current Security Threats in The National and International Context - Cristea Lavinia Mihaela (Journal of Accounting and Management Information Systems (JAMIS), 2020)
Research Question: What are the main security threats emphasized by national and international surveys? Motivation: The rapid growth of IT brings worldwide security issues (Takahashi et al., 2010; Benjamin et al., 2015). IT usage brings new challenges (e.g. higher risks of data exposure, sensitive corporate data, phishing, electronic fraud, impersonations, information security issues) (Morrow, 2012; Thielens, 2013; Rînda?u, 2016), cybercrime being a "sophisticated transnational threat operating on an industrial scale" (Hunton, 2012: 203). Idea: This paper intends to underline the great exposure of financial and non-financial information in the new cybersecurity context, indicated by IT impact on security threats and cyberattacks. Data: The author traced the analysis of the most frequent cyber threats, over a period of six years (2013-2018), based on 20 security reports. Tools: The author adopts the qualitative method, applying critical observations on emerging technologies impact. A hand-collecting method is required, for the analysis and comparison of cybersecurity threats reports. Findings: This investigation highlights Targeted attacks/ APTs, malware and ransomware on top security threats that continue to disrupt worldwide and Romanian landscape, along with a major rate of employee errors. The paper enhances on the consequences, main security threats and concludes on security cybercrime prevention (i.e. adequate business model implementation, Cloud security solutions, 24/7 monitoring for continuous protection, continuous IT security training, implemented modules against a variety of security incidents, regular updates). Contribution: By bringing to the fore actual security issues, the author concludes on main security threats and completes previous specialized works on security against cybercrime.
Keywords: M41; 650; cybersecurity attacks; cybercrime prevention; top cyberattacks; current security threats